Near-infrared triggered injectable ferrimagnetic chitosan thermosensitive hydrogel for photo hyperthermia and precisely controlled drug release in tumor ablation. (5th January 2022) - Zhang, Lichuang; Guan, Xiali; Xiao, Xiongfu; Chai, Yixin; Chen, Zhigang; Zhou, Gang; Fan, Yubo
Graphical abstract: Highlights: Ferrimagnetic chitosan hydrogel (FCH) was established to prevent leakage of IONCs. NIR triggered efficient hyperthermia and precisely heat-responsive drug release. FCH@DOX showed synergistic killing effect on tumor cells under NIR irradiation. Abstract: The combination of photothermal therapy (PTT) and chemotherapy has been a promising strategy for clinical cancer treatment, but traditional platforms using photothermal agents as drug carriers are poor at continuous fixation at the tumor site, often resulting in undesired thermal damage to surrounding healthy tissues and toxicity due to uncontrolled drug leakage. To provide an alternative strategy, an injectable ferrimagnetic chitosan thermosensitive hydrogel was developed in this study. The prepared hydrogel exhibited the gelation ability at 37℃ and long term stability in PBS solution. The firmly embedded photothermal agent iron oxide nanocubes (IONCs) endowed the chitosan hydrogel with excellent hyperthermia performance under near-infrared (NIR) triggering, and thus realized precisely responsive controlled release of loaded drugs. Compared with the pure photo hyperthermia and DOX therapies, ferrimagnetic chitosan hydrogel loaded with DOX showed synergistic effect and sustained treatment in tumor cells killing. Furthermore, the good biocompatibility of the hydrogel also ensured its application as a tumor ablation material.